Approximations to the Experience of the Manuel Rodríguez Patriotic Movement (1991-2006); Aproximaciones a la Experiencia del Movimiento Patriótico Manuel Rodríguez (1991-2006) - Velasquez-Meza, J (Universidad de Playa Ancha -Departamento De Historia, 2025)
This article analyzes the experience of the Movimiento Patriótico Manuel Rodríguez (MPMR), from its formation under the Communist Party of Chile in 1991, during the period of democratic transition, until its definitive break with the historical matrix of Rodriguismo in the country in 2006. It highlights its evolution within the national political-social context, as well as its insertion in the Latin American scenario allowing a greater openness in the political discussion compared to the clandestinity of the dictatorship. Throughout the 1990s and early 2000s, the MPMR experienced various tensions, facing the challenges of readjustment tacitly imposed by the post-dictatorship, generating new ways of understanding and doing politics. In addition, we examine the persistence of the MPMR as a political identity in dispute, which, far from fading away, bet on continuing to intervene in the political and social reality of the country, integrating the revolutionary memory with new strategies and identity formulations, demonstrating its adaptation to the new times. © 2025 Universidad de Playa Ancha -Departamento De Historia. All rights reserved.